The Relationship between Mental Health Awareness and Stress Coping Strategies in Employees - May Lia Elfina (Journal of Research and Measurement in Psychology: JPPP, 2026)
It is essential to maintain employees’ health conditions, particularly the often-overlooked aspect of mental health. One factor that supports employees’ psychological well-being is their ability to manage and adapt to their environment. This includes being competent in regulating their surroundings, having an interest in participating in environmental activities, and possessing awareness of mental health. Mental health awareness serves as a foundation for individuals to understand their well-being, identify problems, and engage in problem-solving, which can also be referred to as a coping stress strategy. This study is a quantitative research with a correlational design aimed at examining the relationship between mental health awareness and stress coping strategies among employees. The instruments used were the Mental Health Literacy Questionnaire–Short Version for Adults (MHLq-SVa) and the Stress and Coping Inventory (SCI). The study involved 217 employees selected through convenience sampling. The analysis results indicate a significant positive relationship between mental health awareness and employees’ coping stress strategies. This finding suggests that the higher the employees’ mental health awareness, the better their coping stress strategies. The implication of this study highlights the importance of mental health awareness in enhancing employees’ ability to cope with problems, which ultimately contributes to other aspects of work performance.